Case Report: Severe Rashes Associated With Fruquintinib in a Patient With Metastatic Colorectal Cancer - Shu, Yefei; Zheng, Song (Frontiers in Oncology, 2021)
Metastatic colorectal cancer (mCRC) is a common and high-risk malignant tumor. Fruquintinib is a novel small-molecule compound with high selective inhibition of vascular endothelial growth factor (VEGF) receptor (VEGFR) for mCRC for which second-line or higher standard chemotherapy has been ineffective. A female patient with mCRC developed severe rashes after 2 weeks of taking fruquintinib. Considering the relationship between fruquintinib and the rashes, she discontinued taking the drug, and her condition improved. Although fruquintinib has shown good safety and manageable toxicity in previous trials, the patient in the present case developed severe rashes after 2 weeks of taking fruquintinib. The common skin reactions of hand and foot are erythema and paresthesia of hand and foot. Because few people have reported a severe rash caused by fruquintinib, which is different from the common hand foot skin reaction. We hope the case attracts the attention of oncologists.